Regulatory T cells safeguard liver health during metabolic-associated steatohepatitis - Bola S. Hanna; P. Kent Langston; Miguel Marin-Rodero; Ricardo N. Ramirez; Min Wan; Christophe Benoist; Diane Mathis (Proceedings of the National Academy of Sciences, 2026)
Metabolic-dysfunction-associated steatohepatitis (MASH) is a chronic liver disease driven by the confluence of metabolic stress and destructive inflammation. The immunoregulatory mechanisms that temper this process remain poorly understood. Multipronged data on a complementary pair of murine MASH models and published single-cell RNA-sequencing datasets from MASH patients revealed a critical protective role for Foxp3 + CD4 + regulatory T cells (Tregs) in MASH. Tregs progressively accumulated in diseased livers, adopting an activated, nonlymphoid-tissue phenotype marked by expression of the transcription factor Peroxisome Proliferator-Activated Receptor Gamma (PPARγ) as well as a reparative transcriptional program. Punctual ablation of Tregs during established MASH unleashed a catastrophic inflammatory cascade, including exaggerated T-helper (Th)1, Th2, and Th17 responses, expansion of a pathogenic CD8 + T cell population, and hepatocellular injury. Concomitantly, Treg deficiency disrupted key metabolic pathways in the liver, accelerating disease progression. These findings establish Tregs as nonredundant custodians of both immunologic and metabolic homeostasis in the liver, highlighting their promise as targets for temporally tuned immunoregulatory therapies in metabolic liver disease.